ANALISIS PENGARUH INVESTASI SWASTA DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI KALIMANTAN BARAT TAHUN 2007 2011 - B01108070, Rachmawati Fitri (Jurnal Pembangunan dan Pemerataan, 2013)
Thesis with the title "The Effect of Private Investment and Economic Growth Against Government Spending District / City of West Kalimantan, 2007-2011". The purpose of this study was to analyze the effect of private investment and spending on economic growth ernment districts / cities in West Kalimantan. This study uses quantitative methods, namely by processing secondary data which is then carried out an analysis of the research object in accordance with the research objectives. The data used are secondary data period 2007-2011 are sourced from the Bureau of Local Government Finance of West Kalimantan and West Kalimantan, Central Bureau of Statistics. From the test results it can be seen that F Private Investment and Government Spending no significant effect on Economic Growth districts / cities in West Kalimantan. Based on the results of the t test, private investment does not significantly affect economic growth, while government spending significantly influence economic growth. Keywords: Economic Growth, Private Investment and Goverment Spendin